Tuberculosis and cardiovascular disease: linking the epidemics. Issue 1 (December 2015) - Huaman, Moises; Henson, David; Ticona, Eduardo; Sterling, Timothy; Garvy, Beth
Abstract The burden of tuberculosis and cardiovascular disease (CVD) is enormous worldwide. CVD rates are rapidly increasing in low- and middle-income countries. Public health programs have been challenged with the overlapping tuberculosis and CVD epidemics. Monocyte/macrophages, lymphocytes and cytokines involved in cellular mediated immune responses againstMycobacterium tuberculosis are also main drivers of atherogenesis, suggesting a potential pathogenic role of tuberculosis in CVD via mechanisms that have been described for other pathogens that establish chronic infection and latency. Studies have shown a pro-atherogenic effect of antibody-mediated responses against mycobacterial heat shock protein-65 through cross reaction with self-antigens in human vessels. Furthermore, subsets of mycobacteria actively replicate during latent tuberculosis infection (LTBI), and recent studies suggest that LTBI is associated with persistent chronic inflammation that may lead to CVD. Recent epidemiologic work has shown that the risk of CVD in persons who develop tuberculosis is higher than in persons without a history of tuberculosis, even several years after recovery from tuberculosis. Together, these data suggest that tuberculosis may play a role in the pathogenesis of CVD. Further research to investigate a potential link between tuberculosis and CVD is warranted.